Characterization of rutin, phenolic compounds and antioxidant capacity of pulps and by-products of tropical fruits (Research, Society and Development, 2020)
In recent years the consumption of tropical fruits has increased, mainly due to their health benefits. This study aimed to identify and quantify the content of rutin using high performance liquid chromatography (HPLC) and other bioactive compounds in the pulp and in the by-products of tropical fruits from Brazil (acerola, guava, mango and caja-umbu). The levels of total polyphenols (Folin-Ciocaulteau), yellow flavonoids, anthocyanins and total antioxidant activity (ABTS method) were also analyzed. The results shows the large amount of bioactive compounds found in by-products, that have beneficial properties for health, and which are mostly wasted. The presence of rutin was observed in all pulps and by-products, but it was highest in the by-product of caja-umbu and acerola pulp. This study provides new information about the content of rutin in the pulp and by-products of tropical fruits, which is essential for future applications in the food industry. Moreover, it contributes to the recovery of by-products from the agro-industrial process.